Functional Literacy, Heterogeneity and the Returns to Schooling : Multi-Country Evidence - Fasih, Tazeen; Patrinos, Harry Anthony; Sakellariou, Chris (World Bank, Washington, DC, 2014)
Little is known about which of the skills that make up workers' human capital contribute to higher earnings. Past empirical evidence suggest that most of the return to schooling is generated by effects or correlates unrelated to the skills measured by the available tests. This paper uses the International Adult Literacy and the Adult Literacy and Life Skills surveys to obtain multi-country estimates of the components of the return to schooling. The results reveal considerable heterogeneity and a dichotomy between two groups of countries. For a subgroup of educationally advanced countries, nearly half of the return to schooling can be attributed to labor marker-relevant functional literacy skills associated with schooling, while for a subgroup of less educationally advanced countries, such skills account for just over 20 percent of the return to schooling, while the return to schooling mostly reflects the signaling value of schooling.